Workplace wellbeing: understanding the context of remote work environments - Hennigan, Rowena (Henry Stewart Talks, 2025)
History of modern workplaces and remote working, Online working environments, wellbeing and leadership, Post-pandemic move to remote work, New models of employment, Pandemic